Foundations for Forecasting: Defining Baseline Seismicity at Fuego Volcano, Guatemala - Brill, Kyle A.; Waite, Gregory P.; Chigna, Gustavo (Frontiers in Earth Science, 2018)
Accurate volcanic eruption forecasting is especially challenging at open vent volcanoes with persistent low levels of activity and relatively sparse permanent monitoring networks. We present a description of seismicity observed at Fuego volcano in Guatemala during January of 2012, a period representative of low-level, open-vent dynamics typical of the current eruptive period. We use this time to establish a baseline of activity from which to build more accurate forecasts. Seismicity consists of both harmonic and non-harmonic tremor, rockfalls, and a variety of signals associated with frequent small emissions from two vents. We categorize emissions into explosions and degassing events (each emitted from both vents); the seismic signatures from these two types of emissions are highly variable. We propose that both vents partially to fully seal between explosions. This model allows for the two types of emissions and accommodates the variety of seismic waveforms we recorded. In addition, there are many small discrete events not linked to eruptions that we examine in detail here. Of these events, 183 are classified into 5 families of repeating, pulse-like long period (0.5–5 Hz) events. Using arrival times from the 5 families and other high-quality events recorded on a temporary, nine-station network on the edifice of Fuego, we compute a 1-D velocity model and use it to locate earthquakes. The waveforms and shallow locations of the repeating families suggest that they are likely produced by rapid increases in gas pressure within a crack very near the surface, possibly within a sealed or partially sealed conduit. The framework from this study is a short but instrument intense observation period, activity description, seismic event detection, velocity modeling, and repose period analysis. This framework can act as a template for augmenting monitoring efforts at other under-studied volcanoes. Even relatively limited studies can at a minimum aid in drawing parallels between volcanic systems and improve comparisons.